Pop Stars as Ambassadors of Sephardic Culture at the Festival Sefarad in Montreal - Roda, Jessica (Contemporary Jewry, 2015)
On their arrival in Montreal, Moroccan Jews established themselves as a community and created a festival in order to promote, gain recognition of, and institutionalize their culture and identity into the broader Jewish community of Montreal. In this article, I propose to analyse the festival as a “thing” (Kopytoff 1986), the biography of which will give us information about its transformation, in terms of representation, through time. From ethnography and historical analysis of the festival, as well as an examination of cultural policies in Canada, Quebec and Montreal during the last decades, we will discover that Sephardic musical heritage, which was initially used for community celebration, was progressively transformed into a marketable product embodied by international pop stars. The representation of Sephardic identity transitioned from a specific cultural reference to Morocco, to Judeo-Spanish and Judeo-Arabic songs, to a plethora of references promoted by Sephardic pop stars, mainly from France and Israel. More broadly, this study will illuminate issues surrounding strategies implemented by the community leaders to be part of these cultural policies and gain visibility in the public sphere.
Keywords: Festival; Montreal; Morocco; Representation; Sephardic; Stars

Creative layers and continuities: A case study of Nicole Lizée and the Kronos Quartet - Bayley, Amanda; Lizée, Nicole (Musicae Scientiae, 2016)
This study examines the creative layers and continuities evident within the composition and rehearsal processes of Nicole Lizée’s Golden Age of the Radiophonic Workshop (Fibre-Optic Flowers), written for the Kronos Quartet in 2012. Lizée’s compositional approach to the historic and the new, and the mechanical and the human, are interpreted through Simon Emmerson’s three themes of combination, transformation, and control, and his three “impulses within composition” that combine live and acousmatic soundworlds – integration, antithesis, and co-existence. These concepts also help to articulate the way the players engage with the physical, psychological, and expressive demands of the piece. Discussions arising from the Kronos Quartet rehearsing the piece with the composer reveal how extensions are made to the performers’ mind and body experiences when they are required both to initiate and integrate sounds emanating from unfamiliar, analogue machines into their acoustic, yet amplified soundworld. Creative layers and continuities are seen to evolve from compositional experimentation and from composer–performer and co-performer dialogues in rehearsal in the BBC Maida Vale studio prior to the world premiere at a BBC Prom concert on 24 July 2012.
Keywords: Delia Derbyshire; Kronos Quartet; Radiophonic Workshop; composition; creativity; electronic sounds; interaction; notation; rehearsal; string quartet

"The Cult of the Diva" – Rufus Wainwright as Opera Queen - Smith, Oliver C. E. (Transposition. Musique et Sciences Sociales, 2013)
The music of Rufus Wainwright has been afforded much critical acclaim thanks to the singer-songwriter’s understanding of Queer cultural history, and the candor with which he explores (homo)sexuality in his music. This case study seeks to examine his use of opera in particular, and how Wainwright uses the historical trope of the opera queen to incorporate his own queerness into music, thus asserting an authority of difference and challenging the dominant (hetero)norm constructions of masculinity in popular music. Wainwright disregards any cultural framework imposed by heternormativism, and reclaims the Orphic figure of operatic authority as one of queer power through this absence. By drawing on his own relationship with opera, Wainwright exploits the right this gives him by reinterpreting cultural history, and revising the pejorative stereotype that is an opera queen.
Keywords: Eurydice; Hallelujah; Jeff Buckley; Memphis Skyline; Rufus Wainwright; Waiting For A Dream; Want Two; diva; gay; heteronormativism; identity; masculinity; opera; queer; stereotype

True Loves, Dark Nights: Queer Performativity and Grieving Through Music in the Work of Rufus Wainwright - Salerno, Stephanie (Université d'État de Bowling Green, 2016)

Cross-dressing to Backbeats: An Exploration of the Practices, Wo/men Producers, and History of Electroclash - Madden, David (Université Concordia, 2013)
This research-creation dissertation focuses on the emergence of electroclash as a dominant form of electronic dance music in the late 1990s and early 2000s. Electroclash combines the extended pulsing sections of techno, house and other dance musics with the trashier energy of rock and new wave. The genre signals an attempt to reinvigorate dance music with a sense of sexuality, personality and irony. Electroclash also emphasizes, rather than hides, the European, trashy elements of electronic dance music. This project addresses the following questions: what is distinct about the genre and its related practices, both in and out of the studio? Why do rock and electro come together at this point and in this way? Why is electroclash affectively powerful for musicians, audiences and listeners? And, what does the genre portend in terms of our understandings of the politics of electronic music? The coming together of rock and electro is examined vis-à-vis the ongoing changing sociality of music production/distribution and the changing role of the producer. Numerous women, whether as solo producers or in the context of collaborative groups, significantly contributed to shaping the aesthetics and production practices of electroclash, an anomaly in the history of popular music and electronic music where the role of the producer has typically been associated with men. These changes are discussed in relation to the way key electroclash producers often used a hybrid approach to production involving the integration of new(er) technologies, such as laptops containing various audio production software with older, inexpensive keyboards, microphones, samplers and drum machines to achieve the ironic backbeat laden hybrid electro-rock sound.

Choral, Public and Private Listener Responses to Hildegard Westerkamp's École - McCartney, Andra; McCarthy, Marta (Music and Arts in Action, 2012)
Hildegard Westerkamp's (1990) composition École Polytechnique is an artistic response to one of Canada's most profoundly disturbing mass murders, the 1989 slaying of fourteen women in Montreal, Quebec. Using the theoretical model, derived from Haraway, of the cyborg body, and analyzing the import of the mixed media (voices, instruments and electroacoustic tape) incorporated in the music, the authors examine the impact this work has had on some of those who have heard it and performed it, based on the responses of choristers and listeners in several studies. The authors explored how those who engaged significantly with the music, (including those who had no personal association with the actual events of the 1989 massacre), were able to make relevant connections between their own experience and the composition itself, embrace these connections and their disturbing resonances, and thereby experience meaningful emotional growth.

Providing the Taste of Learning: Nadia Boulanger’s Lasting Imprint on Canadian Music - Boivin, Jean (Intersections: Canadian Journal of Music / Intersections : revue canadienne de musique, 2013)
This article traces the rich Canadian legacy of the twentieth-century French musical legend Nadia Boulanger (1887–1979). Through teaching her more than seventy Canadian students, both French- and English-speaking, the renowned French pedagogue played a crucial role in the development of concert art music in this country from the 1920s, notably in Montreal and Toronto. Her numerous Canadian students went on to distinguish themselves as composers, teachers, performers, musicologists, theorists, administrators, and radio producers. Drawing on extensive archival and primary research, this study demonstrates the decisive impact Boulanger had on the development of musical styles and compositional practices in Canada in the last century.

From Kitchen To Carnegie Hall: The Story of the Montreal Women's Symphony Orchestra - Rachwal, Maria Noriega (Second Story Press, 2015)
In the 1940s it was unheard of for women to be members of a professional orchestra, let alone play "masculine" instruments like the bass or trombone. Yet despite these formidable challenges, the Montreal Women's Symphony Orchestra (MWSO) became the only all-women orchestra in Canadian history. Formed in 1940, the MWSO became the first orchestra to represent Canada in New York City's Carnegie Hall and one of its members also became the first Canadian black woman to play in a symphony in Carnegie Hall. While the MWSO has paved the way for contemporary female musicians, the stories of these women are largely missing from historical records. From Kitchen to Carnegie Hall illuminates these revolutionary stories, including the life of the incredible Ethel Stark, the co-founder and conductor of the MWSO. Ethel's work opened doors of equal opportunity for marginalized groups and played an important role in breaking gender stereotypes in the Canadian music world.
Keywords: History / Canada / Post-Confederation (1867-); Music / History & Criticism; Music / Individual Composer & Musician

The “Manic Pixie Dream Girl of the Synth-Pop World” and Her “Baby Doll Lisp”: Grimes and the Disabling Logics of the Feminization and Infantilization of Lisping - Holmes, Jessica A. (Journal of Popular Music Studies, 2019)
Audible in speech and song, electro-pop singer Grimes’s so-called “baby doll” lisp generates endless buzz online, ranging from light-hearted adoration, to infantilization, to sexual fetish and even to ableist, misogynist anti-fandom. This article uses the reception of her lisp to build an intersectional theory of lisping across its medical and socio-cultural constructions, bridging work in disability studies, dysfluency studies, voice studies, and popular music studies in the process. I situate the slippage between adoring, infantilizing, fetishistic, and violent characterizations of Grimes’s lisp as reflective of the infantilization of “communicative disorders” in speech language pathology, and the dysfunction associated with feminine coded-speech patterns (e.g. vocal fry and up talk) in the popular imaginary. Lisping is profitably understood as an audible form of “liminal” difference relative to visible physical disabilities (St. Pierre), and to certain ableist, gendered, and racialized conceptions of normative vocality. Ultimately, in the English-speaking world, the lisp is symbolically-coded feminine while exceeding the norms of female vocality, thereby giving rise to a polarizing set of associations that work against female authority and, by extension in Grimes’s case, female musical authorship. Grimes’s reception thus offers a valuable case study for interrogating how misogynist fantasies regarding femininity are thought localized in the female voice, and the symbolic ties between disability and femininity.

Cool Control, Occam, and Océan: The Radigue and Bozzini Game - Majeau-Bettez, Emanuelle (Les Cahiers de la Société québécoise de recherche en musique, 2017)
Cet article analyse la nouvelle collaboration entre la compositrice et pionnière de musique électronique, Éliane Radigue, et le Quatuor Bozzini. Débutant vers la fin des années 1960, la carrière d’Éliane Radigue se caractérise par de très longues oeuvres de musique électronique qui semblent de prime abord ne pas changer, et dans lesquelles les micro-oscillations naturelles entre les hauteurs remplacent la rythmique traditionnelle. Depuis 2001, Radigue ne travaille plus qu’avec des instrumentistes et utilise un « processus de composition intuitif » semblable à la « transmission orale de musiques traditionnelles anciennes » (Sonami 2017). Alors que les quelques intellectuels qui ont fait montre d’intérêt envers la musique de Radigue ont concentré leur attention sur l’aspect oral de ses compositions, cet article cherche ici à amener l’analyse au-delà des paramètres formels « non-écrits » de sa musique afin d’explorer comment la sonorité d’une pièce de Radigue génère de nouvelles manières de concevoir la performance et la composition. Les notes d’observation de l’auteure, la correspondance entre l’auteure, la compositrice et le quatuor, et les enregistrements des rencontres entre les Bozzini et Radigue seront utilisés pour retracer les moments de grande réaction émotionnelle causés par la sonorité très particulière que demande la musique de Radigue. Ces réactions affectives du côté de Radigue et du quatuor révèlent des points de tension entre différentes conceptions de la création collective, et réorientent complètement ce que cela signifie que de posséder, transmettre, interpréter et composer de la musique. Des spectrogrammes et des enregistrements des tentatives entreprises par les Bozzini seront utilisés dans l’étude de ces points de tension, et démontreront qu’afin de pouvoir jouer avec succès une pièce instrumentale de Radigue, les Bozzini doivent reproduire chaque élément des pièces électroniques de la compositrice; le quatuor à cordes doit se « transformer » en un étrange instrument.

Java to Jazz: Eva Gauthier - Spiller, Henry (Javaphilia: American Love Affairs with Javanese Music and Dance, 2015)

Montréal Rave: An Oral History - Borzeix, Olivier (Red Bull Music Academy, 2016)
Tiga, Christian Pronovost, Jeff Waye and more remember the golden era of raves in Montréal.

Robert Ouimet and Pierre Gagnon - Burns, Todd L. (Redd Bull Music Academy, 2016)
Explore the Red Bull Music Academy archive, tracing the global music institution’s more than 20-year history

Reality Sounding: Annesley Black’s not thinking about the elephants - Tan, Anthony (Circuit, 2019)
This paper presents an analysis of Annesley Black’s not thinking about the elephants (2018), for saxophone quartet and live electronics. Written for Montreal’s Quasar Saxophone Quartet, this work explores concepts of suppression and emergence through traditional musical dimensions such as melody, counterpoint, and form, but also through contemporary musical dimensions such as psychoacoustics (difference tones), theatrical elements, and live electronics. Black’s practice engages critically with the compositional process itself by formulating dialectic relationships between material and compositional strategies (both intuitive and systematic). This work encourages the listener to engage in a multidimensional listening experience where conceptual extremes become a catalyst for the building of narrative and tension.

On feeling mighty real: devenir gay à Montréal pendant l’ère disco dans Funkytown, de Daniel Roby - Foerster, Maxime (Contemporary French Civilization, 2018)
Our catalogue of journals

Nightclubbing: Montréal’s Lime Light - Pemberton, Rollie (Red Bull Music Academy, 2016)
The Lime Light and its innovative DJ Robert Ouimet made Montreal a disco city during the ’70s. This is the club's story.

Musical Robots and the Serbian Kolo: A Narrative Analysis of Ana Sokolović’s Géométrie sentimentale (1997) - Harman, Brian (Circuit, 2012)
Composer Ana Sokolović divided her instrumental work Géométrie sentimentale into large sections inspired by pure geometric shapes — Triangle, Cercle and Carré — describing these sections as three contrasting perspectives of the same musical materials. This article uses a narrative analytical approach as a lens through which to understand these distinct sections and the materials populating them. Inspired by Sokolović’s employment of musical objects in her compositions and by the extra-musical concepts inspiring many of her works, this analysis uses a collection of colourful robot toys as metaphors for the work’s materials. Three unique perspectives of these toys are described: in Triangle, the robots interact as characters on a dramatic stage; in Cercle, they peacefully coexist in slow motion; and in Carré new combinations of robot elements are abruptly juxtaposed against each other. The characteristics and interactions between these toys, as well as the various harmonic ‘masks’ that the composer has them wear, are helpful in understanding Sokolović’s harmonic structure, variation/transformation techniques, formal organization and rhythmic characteristics. The Serbian kolo is also shown as influential on the work, relating directly to the physicality and kinetics of the metaphorical robots.

The Vocal Music of Ana Sokolović: Love Songs for the Twenty-First Century - Bernstein, Tamara (Circuit, 2012)
Enchanted by the vocal music of Serbian-born Canadian composer Ana Sokolović, Tamara Bernstein visited the composer at her home in Montreal. Sokolović’s music draws on several sources, including the theatrical world and the culture of the Balkans. The extended vocal techniques in Sokolović’s music are rooted not in the avant-garde music of the twentieth century, but in the oral traditions and poetic voice of Serbia. It seems that the more the composer returns to her cultural roots, the more she embraces the universality of the human soul.